The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1080/20002297.2020.1838164
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to biofilm formation on 3D-printed titanium fixation plates used in the mandible: a preliminary study

Abstract: Background: In the oral and maxillofacial surgery, fixation plates are commonly used for the stabilization of bone fragments. Additive manufacturing has enabled us to design and create personalized fixation devices that would ideally fit any given fracture. Aim: The aim of the present preliminary study was to assess the susceptibility of 3D-printed titanium fixation plates to biofilm formation. Methods: Plates were manufactured using selective laser me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 76 publications
1
11
0
Order By: Relevance
“…Generally, the rougher surfaces (rough-blasted TiAl6V4, cpTi, cpTi + TCP) showed a higher tendency for the bacterial cells to form more proteins and polysaccharides in their matrix compared to the surfaces appearing smoother (TiAl6V4, TiN, Ag) in the SEM pictures (see also Figure 1 and Table 2). A study by Palka et al (2020) [26] also conclusively showed that rougher surfaces promote the susceptibility to microbial adhesion, amongst other bacterial species as well as for S. aureus and S. epidermidis. Similar findings, but for different base materials (Ti6Al4V, CoCr alloy and zirconium), have been reported by Minkiewicz-Zochniak et al, 2021 [24].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Generally, the rougher surfaces (rough-blasted TiAl6V4, cpTi, cpTi + TCP) showed a higher tendency for the bacterial cells to form more proteins and polysaccharides in their matrix compared to the surfaces appearing smoother (TiAl6V4, TiN, Ag) in the SEM pictures (see also Figure 1 and Table 2). A study by Palka et al (2020) [26] also conclusively showed that rougher surfaces promote the susceptibility to microbial adhesion, amongst other bacterial species as well as for S. aureus and S. epidermidis. Similar findings, but for different base materials (Ti6Al4V, CoCr alloy and zirconium), have been reported by Minkiewicz-Zochniak et al, 2021 [24].…”
Section: Discussionmentioning
confidence: 85%
“…In addition, biocompatibility [19] and resistance to bacterial infections [12,[20][21][22] can be positively influenced by those newly developed materials. As mentioned above, S. aureus and S. epidermidis are especially prone to cause device-related infections, and they are used in many biofilm-related studies in the field of orthopedics [6,[21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…In this proof-of-concept work, we examined K. pneumoniae and E. coli biofilm growth on two different resins (HT and dental) and applied additional coatings of either dental resin or silicone (PDMS), mimicking the surfaces of medical devices. Although unwanted in an in vivo situation with implants (Palka et al, 2020), here, we took advantage of the characteristic surface roughness typical of additive manufacturing. We showed that uncoated 3D-printed pegs with higher surface roughness supported larger population sizes (CFU per peg) and biomass (CV staining) than polystyrene MBEC ™ pegs, making them suitable for fundamental biofilm studies requiring more biomass.…”
Section: Discussionmentioning
confidence: 99%
“…Additive manufacturing, also known as 3D printing, serves as a fast and cost-effective way to manufacture custom-designed objects, including medically relevant products, for example, surgical guides, implants, and other devices (Paul et al, 2018). Some materials used in additive manufacturing of medical devices, such as polylactic acid polymers (Hall et al, 2021) or titanium plates (Palka et al, 2020), have recently been studied for their propensity for bacterial attachment and growth. Microfluidics systems frequently rely on 3D-printed molds for casting silicone (polydimethylsiloxane (PDMS)) chips for biofilm growth (Kim et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, such plates entered maxillofacial surgery; however, the technology of their manufacture makes them have a rough surface. Such a surface is exposed to bacterial invasion by creating a biofilm [ 28 ]. On the other hand, fused ceramic surfaces can be smoother.…”
Section: Discussionmentioning
confidence: 99%